PENGEMBANGAN PERANGKAT UNIT KEGIATAN BELAJAR MANDIRI BERBASIS HIGHER ORDER THINKING SKILLS PADA MATERI POKOK FLUIDA STATIS - Abdul Hamid; Mitri Irianti; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The aim of this research is to develop Unit Kegiatan Belajar Mandiri (UKBM) based on Higher-Order Thingking Skills (HOTS) on static fluid basic material that valid. There are 4 static fluid Unit Kegiatan Belajar Mandiri that developed, namely, 1st UKBM is Hydrostatic Pressure, 2nd UKBM is Pascal's Law, 3rd UKBM is Archimedes Law and 4th UKBM is Surface Tension. This type of research is Research and Development (R&D) using the 4D. The data was collected through the UKBM validation assessment sheet which was filled by the validator. The aspects of UKBM that are assessed include aspects of presentation feasibility, content feasibility, linguistic feasibility and graphic feasibility as well as an assessment of HOTS aspects. The results of the validation of UKBM for Static Fluid obtained an average of 3.50. Thus be concluded that the device Unit Kegiatan Belajar Mandiri (UKBM) based Higher Order Thinking Skiils (HOTS) on static fluid basic material was valid.Keywords: Unit Kegiatan Belajar Mandiri (UKBM), Higher-Order Thinking Skills, Static Fluid UKBM.